2013
DOI: 10.1111/papr.12145
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Descending Inhibitory Pathways on Chronic Pain Modulation and Clinical Implications

Abstract: The treatment and management of chronic pain is a major challenge for clinicians. Chronic pain is often underdiagnosed and undertreated, and there is a lack of awareness of the pathophysiologic mechanisms that contribute to chronic pain. Chronic pain involves peripheral and central sensitization, as well as the alteration of the pain modulatory pathways. Imbalance between the descending facilitatory systems and the descending inhibitory systems is believed to be involved in chronic pain in pathological conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
88
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(92 citation statements)
references
References 122 publications
(173 reference statements)
2
88
0
2
Order By: Relevance
“…Therefore the test results of both arms were combined and averages used for statistical analyses. 13 10 s ramp and hold pressure stimuli were applied to the supraspinatus muscles, the lateral epicondyles, and the gluteal muscles in counterbalanced order. The mean peak pain ratings (eVAS) for fixed pressure stimuli at the beginning and end of the trial are shown in Table 2 A.…”
Section: Quantitative Sensory Test (Qst) Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore the test results of both arms were combined and averages used for statistical analyses. 13 10 s ramp and hold pressure stimuli were applied to the supraspinatus muscles, the lateral epicondyles, and the gluteal muscles in counterbalanced order. The mean peak pain ratings (eVAS) for fixed pressure stimuli at the beginning and end of the trial are shown in Table 2 A.…”
Section: Quantitative Sensory Test (Qst) Resultsmentioning
confidence: 99%
“…Besides their effects on negative affect NSRIs are thought to improve chronic pain through central and peripheral nervous systems mechanisms, including noradrenaline and serotonin neurotransmission, actions on opioid, adrenergic, serotonin, GABA and NMDA receptors, ion channel activation and possible effects on inflammatory cytokines 41 . Additionally, they seem to modulate descending inhibitory pain pathways and central sensitization 13,49 .…”
Section: Introductionmentioning
confidence: 99%
“…46 The regulation of pain signals transiting through the DH of the spinal cord is also under Basic Anatomy and Physiology of Pain Pathways the control of dopaminergic descending neurons from the periventricular region of the hypothalamus (A11). 47 The dopamine receptor subtype expressed by primary afferents or DH neurons in lamina I dictate an antinociceptive or pronociceptive effect. 47 Dysfunction of this descending pain system may lead to chronic pain conditions; however, this descending dopaminergic system is another potential target for treatment.…”
Section: Descending Systemsmentioning
confidence: 99%
“…47 The dopamine receptor subtype expressed by primary afferents or DH neurons in lamina I dictate an antinociceptive or pronociceptive effect. 47 Dysfunction of this descending pain system may lead to chronic pain conditions; however, this descending dopaminergic system is another potential target for treatment. 47 The descending endogenous opioid pain modulation system also augments pain processing.…”
Section: Descending Systemsmentioning
confidence: 99%
“…These pathways arise in multiple areas of the cerebrum and brainstem and inhibit transmission of nociceptive inputs at the level of the dorsal horn. 16 Obviously, it is difficult to draw conclusions with a sample size of one and this patient could very well be an outlier, or simply be evidence that baseline pain is not predictive of evoked pain sensitivity.…”
Section: Proceedings In Obstetrics and Gynecology 2017;7(1):3mentioning
confidence: 99%